Secure Educational Network (International Journal of Engineering and Computer Science, 2017)
Communication has been made possible since human desires to communicate from one corner to another corner. Every way we have used many resources in communication and reached out around the globe. Today communication has been developed for various sectors in a country. In India, primarily in education sector, many schools and colleges have been providing internet facility for students. Our paper deals with one of the security protocol, its – secure educational network to educate students without resisting internet as only the education medium. We call it as – Secure Data Monitor Protocol